PERENCANAAN KARIR PEGAWAI DI BADAN PERTANAHAN NASIONAL RI - Andi Tenri Abeng; Rizal Syarief; Arif Imam Suroso (School of Business, Bogor Agricultural University (SB-IPB), 2016)
This study aims to provide a new perspective on the governance of employee career planning prevailing in BPN RI in which this is alleged to constitute the lethargic and counterproductive atmosphere to the employee performance level. In this study, the writer analyzed the formulation of the indicators of the existing career planning and identified how these indicators should be valued more precisely. Furthermore, the recommended managerial implications for Organization and Civil management of BPN RI were formulated. Analytic hierarchy process (AHP) was utilized to examine the results of in-depth interviews with the experts as the respondents in this study and they were also supported by literature studies. The results showed that there are a number of fundamental flaws identified in the career planning for BPN RI, and they need to be corrected. In reference to AHP analysis, it can be seen that the career pattern is a variable with the highest level of interest in the implementation of career planning. AHP analysis results showed that the type of office is an indicator which has the highest interest rate in career pattern variable while the competence attribute has the highest interest rate in the occupational qualification variable. Moreover, at the entry point variable, educational background is an indicator with the highest interest rate, and so is the indicator of work experience which has the highest value in the career restriction variable. These results indicate that career planning for BPN RI needs to be improved with a primary focus on the implementation of career pattern.Keywords: AHP, BPN RI, career planning factors, career planning variables, indicators of career planningABSTRAKPenelitian ini bertujuan memberikan perspektif baru terhadap tata kelola perencanaan karir pegawai yang berlaku di lingkungan BPN RI yang diduga telah menimbulkan atmosfer kelesuan dan bahkan kontraproduktif terhadap tingkat kinerja pegawai. Dalam hal ini penulis menganalisis perumusan indikator-indikator perencanaan karir yang ada dan bagaimana yang seharusnya dinilai lebih tepat; serta kemudian merumuskan implikasi manajerial yang direkomendasikan bagi manajemen Biro Organisasi dan Kepegawaian BPN RI. Analisis dilakukan dengan menggunakan analytic hierarchy process (AHP) dari hasil wawancara mendalam terhadap para pakar yang menjadi responden dalam penelitian ini yang didukung dengan studi literatur. Hasil penelitian menunjukkan, bahwa perencanaan karir di BPN RI masih memiliki beberapa kekurangan mendasar yang perlu dikoreksi. Selain itu berdasarkan hasil analisis AHP, dapat diketahui bahwa pola karir merupakan variabel dengan nilai tingkat kepentingan tertinggi dalam pelaksanaan perencanaan karir. Hasil analisis AHP tidak menunjukkan bahwa tipe kantor merupakan indikator yang memiliki nilai tingkat kepentingan tertinggi dalam variabel pola karir, sementara indikator atribut kompetensi memiliki nilai tingkat kepentingan tertinggi dalam variabel kualifikasi jabatan. Sedangkan pada variabel entry point, indikator latar belakang pendidikan merupakan indikator dengan nilai tingkat kepentingan paling tinggi dan begitu pula indikator pengalaman kerja yang menjadi indikator dengan nilai tertinggi pada variabel batasan karir. Hasil ini menunjukan bahwa perencanaan karir di BPN RI perlu diperbaiki dengan fokus utama pada pelaksanaan pola karir.Kata kunci: AHP, BPN RI, faktor perencanaan karir, indikator perencanaan karir, variabel perencanaan karir